(untitled) (MedS Alliance Journal of Medicine and Medical Sciences, 2024)
Introduction: Claudin-5(CLDN-5) is one of the principal proteins predominantly expressed at blood-brain barrier (BBB) and plays an important role in tight junction (TJ) formation and maintaining the integrity of BBB. Thus, this study was designed to study the association of polymorphism rs1548359, rs10314, and rs739371 at CLDN-5 gene and leukoaraiosis in the Korean population. Materials and Methods: A real-time PCR, a LightSNiP typing assay (coupled with primer and probe, TIB-MolBiol, Berlin, Roche Applied Science, Germany) was used to detect the genotypes of CLDN-5. Logistic regression analyses and stratification analyses with adjustment for traditional risk factors (age, sex, diabetes and hypertension) were used to find the genetic effect. Results: We did not find any significant association for overall leukoaraiosis or any subtype analyses. Analyses of both leukoaraiosis subtypes (PVWM and DWM) did not show any significant associations (p = 0.29-0.59). Conclusions: CLDN-5 polymorphisms may not play a significant role in the development of leukoaraiosis in the studied population. However, further replications in different ethnic groups and larger populations are recommended.